ANALISIS PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI PELAYANAN PUBLIK BERBASIS WEB - Suroto - (JURNAL AKADEMIKA)
This study conducted due to the low quality indicator of public services in indonesia which are difficult to be accessed. On the other side, the spirit of decentralization and reformation demanding changes of the role of government and society. Therefore, good governance should be implemented in all development aspects such as licensing which is the most important equipment for Local Governance and it is potential to increase Regional Revenue. Integrated Licensing Service Office as an instituition which in charge of granting license in Tanjung Jabung Timur must be able to meet the public's expectations of quick, inexpensive and transparent services. It relates to the lack of sustainable program planning preparation considering computerized system integrated with current information system.